COGNITIVE SIGNS OF THE CONCEPT OF INSULT IN THE ENGLISH LANGUAGE (American Journal of Interdisciplinary Research and Development, 2024)
The article discusses the cognitive signs of the concept of insult depicted in the English proverbs and quotations. The purpose of the research is to identify and analyze the linguistic units that make up the paremiological field of the concept insult in the English language. The article uses the method of conceptual analysis, proposed by I. A. Sternin.